An Elegant Synthesis of Pyrano-Bisquinaldines - Suresh, T.; Nandha Kumar, R.; Mohan, P.S. (Asian Journal of Chemistry, 2010)
A solution of 4-hydroxy-2-methylquinoline in 2% sodium hydroxide, when treated with vinyl acetate, yielded pyrano-bisquinaldine. The structures of these compounds have been characterized by their spectral and analytical data.